2022
DOI: 10.3390/plants11030409
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of SaCLCd, SaCLCf, and SaCLCg, Novel Proteins of the Chloride Channel Family (CLC) from the Halophyte Suaeda altissima (L.) Pall

Abstract: Coding sequences of the CLC family genes SaCLCd, SaCLCf, and SaCLCg, the putative orthologs of Arabidopsis thaliana AtCLCd, AtCLCf, and AtCLCg genes, were cloned from the euhalophyte Suaeda altissima (L.) Pall. The key conserved motifs and glutamates inherent in proteins of the CLC family were identified in SaCLCd, SaCLCf, and SaCLCg amino acid sequences. SaCLCd and SaCLCg were characterized by higher homology to eukaryotic (human) CLCs, while SaCLCf was closer to prokaryotic CLCs. Ion specificities of the SaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 78 publications
2
15
0
Order By: Relevance
“…OM994379, accordingly). This approach led earlier to cloning of 5 CLC genes from S. altissima [ 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…OM994379, accordingly). This approach led earlier to cloning of 5 CLC genes from S. altissima [ 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cloned cDNAs of the SaCLCa2 and SaCLCc2 genes contained open reading frames (ORFs) encoding polypeptides consisting of 800 and 708 amino acids, with calculated molecular masses of 88.2 and 77.5 kDa, respectively. Amino acid sequences of the SaCLCa2 and SaCLCc2 were aligned with those of other SaCLC proteins revealed by us previously [ 31 , 32 , 33 ]. The SaCLCa2 protein is comparable in size with SaCLCa1 (811 a.a.), SaCLCc1 (791 a.a.), SaCLCd (793 a.a.), and SaCLCg (776 a.a.) ( Figure 1 ), as well with AtCLCa (775 a.a.), AtCLCb (780 a.a.) [ 36 ], and a protein encoded by a sequence found in S. fruticosa transcriptome, SfCLCa2 (800 a.a.) ( Figure S1a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Suaeda altissima (L.) Pall., the expression of chloride channel (CLC) family genes SaCLCc1 , SaCLCd , SaCLCf and SaCLCg in leaves increased with the increase of salt concentration, consistent with the accumulation of Cl − in leaf cells. The results indicated that SaCLCc1, SaCLCd, SaCLCf and SaCLCg proteins may be involved in the separation of Cl − in organelles, and may be involved in the mechanism of salt tolerance [ 42 , 43 ]. In addition, the complementation assay and bioinformatic analyses indicated that SaCLCc1 and SaCLCd proteins are Cl − /H + antiporters, while the SaCLCf and SaCLCg proteins are likely Cl − channels [ 42 , 43 ].…”
Section: Ion Regulation and Compartmentationmentioning
confidence: 99%
“…The results indicated that SaCLCc1, SaCLCd, SaCLCf and SaCLCg proteins may be involved in the separation of Cl − in organelles, and may be involved in the mechanism of salt tolerance [ 42 , 43 ]. In addition, the complementation assay and bioinformatic analyses indicated that SaCLCc1 and SaCLCd proteins are Cl − /H + antiporters, while the SaCLCf and SaCLCg proteins are likely Cl − channels [ 42 , 43 ].…”
Section: Ion Regulation and Compartmentationmentioning
confidence: 99%